A validation study of the International Trauma Questionnaire to assess post-traumatic stress disorder in treatment-seeking veterans. (March 2020) - Murphy, Dominic; Shevlin, Mark; Pearson, Emily; Greenberg, Neil; Wessely, Simon; Busuttil, Walter; Karatzias, Thanos
Abstract : Background: Veterans with post-traumatic stress disorder (PTSD) typically report a poorer treatment response than those who have not served in the Armed Forces. A possible explanation is that veterans often present with complex symptoms of PTSD. ICD-11 PTSD and complex PTSD (CPTSD) have not previously been explored in a military sample. Aims: This study aimed to validate the only measure of ICD-11 PTSD and CPTSD, the International Trauma Questionnaire, and assess the rates of the disorder in a sample of treatment-seeking UK veterans. Method: A sample of help-seeking veterans ( N = 177) was recruited from a national charity in the UK that provides clinical services to veterans. Participants completed measures of ICD-11 PTSD and CPTSD as well as childhood and adult traumatic life events. Confirmatory factor analysis was used to assess the latent structure of PTSD and CPTSD symptoms, and rates of the disorders were estimated. Results: The majority of the participants (70.7%) reported symptoms consistent with a diagnosis of either PTSD or CPTSD. Results indicated the presence of two separate disorders, with CPTSD being more frequently endorsed (56.7%) than PTSD (14.0%). CPTSD was more strongly associated with childhood trauma than PTSD. Conclusions: The International Trauma Questionnaire can adequately distinguish between PTSD and CPTSD within clinical samples of veterans. There is a need to explore the effectiveness of existing and new treatments for CPTSD in military personnel.